Effect of heat input on the microstructure and hardness of AISI 321 stainless steel welds using ER 347 filler metal - Oktadinata, Herry; Purnama, Dewin; Anugrah, Debby Laksana (Jurnal Polimesin, 2024)
Stainless steel is widely used in various fields, one of which is AISI 321, which is used for high-temperature applications because of its high resistance to creep and intergranular corrosion. The type of filler metal and heat input on stainless steel welds play an essential role in determining the microstructure and mechanical properties of the welded joints. The purpose of this experiment was to evaluate the microstructure and mechanical properties of AISI 321 stainless steel welds with variations in heat input. This study is expected to explore the performance of this weld joint, which can be anticipated in relevant fields. The welding method used in this experiment was Gas Tungsten Arc Welding (GTAW) with ER 347 as filler metal. Welding was carried out on three samples with a heat input of 0.92 kJ/mm, 0.64 kJ/mm, and 0.52 kJ/mm, respectively. The tests included tensile strength, Vickers microhardness, and microstructure observations. The tensile test results showed that a fracture occurred in the Base Metal (BM) area, indicating that the strength of the weld joint was higher than that in the BM. The Vickers microhardness test results showed that the Weld Metal's hardness (WM) was the highest, followed by the Heat-Affected Zone (HAZ) and BM. The welding experiment that used three variations in heat input demonstrated that higher heat input lowered the hardness of the weld joint. The microstructure observation results around the fusion line demonstrated the presence of step and ditch structures. The ditch structure indicates intergranular corrosion.